Key public verifiable MA-CP-ABE scheme based on aggregatable PVSS and consortium blockchain - JING Xu; JIANG Yan (Tongxin xuebao, 2024)
To address challenges associated with threshold-based multi-authority ciphertext-policy attribute-based encryption (MA-CP-ABE), such as untrusted attribute authorities (AA) and the inability to verify the correctness of attribute private keys publicly, a key public verifiable MA-CP-ABE scheme based on aggregatable publicly verifiable secret sharing (PVSS) and consortium blockchain was proposed. An aggregatable PVSS algorithm was improved based on ElGamal, which enabled the public verifiability of the system master key distribution. A publicly verifiable method for MA-CP-ABE attribute private keys was constructed based on bilinear maps and ElGamal encryption, enabling the public verifiability of attribute private keys and their shares in ciphertext conditions. A key public verifiable MA-CP-ABE scheme was proposed based on a consortium blockchain, ensuring the trustworthiness of verification parameters through the consortium blockchain and achieving automated verification via smart contracts. The analysis of correctness, confidentiality, robustness, and liveness indicates that when the total number of AA is n, the threshold value is t, and the number of malicious AA is not more than t-1, the scheme can ensure the correct distribution of attribute private keys, and the communication overhead complexity of the system master key initialization is O(tn).